(untitled) (Fiep Bulletin - online, 2014)
Objective: To identify the epidemiologic profile of adults with cancer living in the city of Sousa-PB. Method: Epidemiological, descriptive and field as a backdrop to the urban and rural municipality cited which data collection was carried out in the year 2102, 60 patients from a questionnaire previously validated. Results: The sample consisted mostly of women (68%), aged 30-80 years (100%), married (68%), low education (94%), non-white skin (42%) and income of a minimum wage (73%). Regarding the type of cancer, the most frequently reported were breast cancer (36%) and skin (16%). Still, the diagnosis was made in the last three years (75%), therapeutic regimens chemotherapy (47%), half showed adverse reaction (50%) and the main risk factor is heredity (53%). Conclusion: It is fundamental to creation of strategies to facilitate patient access to health services for effective therapy, since early diagnosis associated with therapy provides a cure and improving the quality of life of patients neoplastic.